The Influence Of Work Motivation And Leadership On Performance: Empirical Study Of Savings And Loans Cooperative Employees In Pemalang - Sabar Iman; Addin Widi Wicaksono; Tina Ika Vidyana (Universitas 17 Agustus 1945 Semarang, 2024)
This research investigates the impact of work motivation and leadership, mediated by job satisfaction, on employee performance in savings and loan cooperatives during the Covid-19 pandemic in Pemalang. The population consists of employees from Koperasi Simpan Pinjam Muti Artha Utama, Graha Mandiri, and Merdeka Makmur the Main Branch Office in Pemalang, totaling 250 individuals. Data collection is conducted through a questionnaire, and the validity and reliability of the instruments are assessed through appropriate tests. The analytical approach involves multiple regression analysis. The findings from the multiple regression analysis indicate that work motivation positively and significantly affects employee performance, while leadership also demonstrates a positive and significant impact on employee performance. Furthermore, work motivation is found to exert a positive and significant influence on job satisfaction, and leadership similarly shows a positive and significant impact on job satisfaction. Job satisfaction is then identified as having a positive and significant effect on employee performance. The results suggest that job satisfaction serves as a mediator, enhancing or fortifying the influence of work motivation variables on employee performance. Similarly, job satisfaction acts as a mediator, amplifying the impact of leadership variables on employee performance within savings and loan cooperatives in Pemalang.